Pelatihan Pengoperasian dan Pemeliharaan Mesin Pengolah Sagu bagi Masyarakat Pemerhati Sagu di Jayapura - Tri Gunaedi; Irma Rahayu (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Training on the operation and maintenance of sago processing machines for the community of sago observers in Jayapura, is the implementation of the implementation of the science and technology application program launched by the Institute for Research and Community Service, University of Cenderawasih in 2022 on July 5, 2022 at the Central Laboratory for the Study of Sago Technology-FMIPA -Cenderawasih University. The sago machines used are sago stick threshing machine, sago stem fall extraction machine, wet sago flour pressing machine and dry coarse sago flour flour machine. The training participants have been able to operate and maintain the sago machine well, as evidenced by the results of sago processing reaching 70%. The results showed that the machine used was effective and efficient in processing sago stalks into dry sago flour. It also proves that the equipment is very easy to operate by the trainees.Â Keywords: sago processing machine